Water Privatization Discourse in Indonesia: Legal Issues and Lessons Learnt from the UK’s Experience - Hidayat, Al Fatah (Indonesian Comparative Law Review, 2023)
Legal protection of water resources is important as a rule and guidelines for human behavior as the purpose of the law to regulate public order. Legal developments regarding water resources need to be updated following the development of the community, so that the creation of legal protection for water resources can have an impact on water conservation. This study examines the policy of legal protection of water resources in Indonesia. It discusses the existing legal issues emerged in water privatization. Besides, it also explores the UK’s experience including the management and policy on the water exploitation. This study employed doctrinal legal research utilizing comparative, statutory, and conceptual approach. The discussion's findings demonstrate that the UK's approach to water management differs from Indonesia's. A system of water privatization is used in UK water regulation. The UK places a high focus on service quality and access to clean water. Therefore, the government offers complaint services regarding water quality in order to regulate the performance of the private sector. The Consumers Council for Water (CCWater) also provides assistance to consumers in homes and businesses. Water and sewage users in the UK and Wales are represented by CCWater, which also accepts unresolved complaints.